Wacana “Deep Learning” dalam Kebijakan Pendidikan: Analisis Wacana Kritis terhadap Representasi Guru dalam Artikel Melintas.id - Tuti Sugilestari; Teti Sobari (Fakultas Ilmu Tarbiyah dan Keguruan UIN Sumatera Utara, 2026)
The paradigm shift in Indonesian education demands the implementation of learning models that foster higher-order thinking skills, one of which is through the concept of Deep Learning adopted in the Merdeka Curriculum. However, behind the rhetoric of innovation, various responses have emerged from educators who question its readiness and relevance to the social realities of national education. This study aims to reveal how the discourse on Deep Learning is constructed and debated in the mass media through an analysis of a news article titled “Deep Learning: Innovation or New Burden? Teachers’ Responses to the Minister of Education’s Breakthrough” published by Melintas.id in 2024. This research employs Norman Fairclough’s Critical Discourse Analysis (CDA) approach by examining three analytical dimensions: (1) the textual dimension, which scrutinizes linguistic structures and ideological representations within the language; (2) the discourse practice dimension, which explores the processes of media text production and consumption; and (3) the sociocultural practice dimension, which links the discourse to broader social contexts and power relations within educational policymaking.The findings indicate that the news text presents a struggle of meanings between the innovation discourse legitimized by the government and the resistance discourse articulated by teachers. The media employs linguistic strategies such as evaluative diction and nominalization to highlight the tension between the idealization of policy and on-the-ground realities. At the level of discourse practice, Melintas.id functions as a reflective media outlet that brings intertextuality into play by connecting national education policy discourse with teachers’ lived experiences. Meanwhile, at the level of sociocultural practice, the reporting reflects ideological disparities between educational modernization and the structural limitations faced by schools. This study concludes that the Deep Learning discourse in the media is not merely a pedagogical issue but an ideological practice that portrays the power relations among the state, teachers, and the media. These findings underscore the importance of critical literacy for educators in understanding education policies not merely as technical procedures but as social constructions infused with values and interests.